Developing Criteria for the Selection of Contemporary Stimulus Material in Mental Health Nursing Education: Engaging Students and Meeting Curriculum Goals - Part 1: Critical Analysis of Simulation and Stimulus Material in Mental Health Nursing Education - Anna Treloar; Margaret McMillan; Teresa Stone; Miran Kim (Halla Newcastle Education and Research Center, 2019)
Purpose By focussing on curricula reliant on blended (online and face-to-face) learning, to test the value of mental health stimulus material created/used by Australians in an Australian context to achieve learning outcomes through assessment tasks for students from a range of cultural backgrounds. Can we find stimulus material that facilitators can use with diverse cultures? Methods Case studies centred on two groups of students - Australian (Part 1) and international (Part 2). Results An analysis of simulation and stimulus material in mental health nursing education (Part 1) and the development of i) a set of principles for choosing 'authentic' stimulus material ii) a set of recommendations for choices of assessment tasks that ensure application of the principles irrespective of the culture and context in which graduates choose to work (Part 2). Conclusion While there are many types of stimulus material available today, authentic stories from clinical practice may also have a useful role in mental health nursing curricula.